2000
DOI: 10.1007/s001340050008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial necrosis in ICU patients with acute non-cardiac disease: a prospective study

Abstract: Hypotension may cause cardiac damage in critically ill patients with acute non-cardiac diseases as shown by abnormal levels of cTnI. It is likely that a high number of these myocardial necroses may go unnoticed on the ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(128 citation statements)
references
References 30 publications
5
108
1
13
Order By: Relevance
“…21 Troponin level is reportedly higher in patients with sepsis and hypotension: 85% and 74%, respectively. 5,22 In our study the highest troponin levels were in the patients with cor pulmonale and COPD: 67% and 66%, respectively. In another study, elevated cardiac troponin was found in 70% of patients with COPD exacerbation.…”
Section: Discussionsupporting
confidence: 46%
“…21 Troponin level is reportedly higher in patients with sepsis and hypotension: 85% and 74%, respectively. 5,22 In our study the highest troponin levels were in the patients with cor pulmonale and COPD: 67% and 66%, respectively. In another study, elevated cardiac troponin was found in 70% of patients with COPD exacerbation.…”
Section: Discussionsupporting
confidence: 46%
“…It was found that the duration of hypotension during sepsis (Arlati et al, 2000) and the vasopressors administered had been found to correlate with the plasma concentration of cTnI, a regulatory protein of the thin actin filament of cardiac muscle (Bertichant et al, 1999). cTnI is a well known diagnostic marker for myocardial injury following congestive heart failure and myocardial infarction (Turner et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Both AKI and myocardial dysfunction are also common in sepsis. [70][71][72] Data have found that 30-80% of septic patients have elevated cardiac-specific troponins [73][74][75] Hepato-Renal syndrome…”
Section: Secondary Cardio-renal Syndromes (Type 5 Crs)mentioning
confidence: 99%